Pencegahan Kebiasaan Merokok di RT 17 Dusun Wonocatur, Banguntapan - Tri Wahyuni Sukesi; Nabila Putri Larasati; Ananda Devi Puspitawati; Nabiila Adhelia Sarasati; Putri Edenia Parawansa; Qonita Qisthina; Elysanti Toring Elma Bura (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
Background: Health problems in a region need to be monitored from year to year and over time, so that the expected information and knowledge do not decrease across different age groups of the population. There is a strong expectation for improved health indicators in every area, especially in regions that are already known for the frequent occurrence of various diseases. Methods: A survey was conducted to collect primary data from residents of RT 17 in order to obtain the results of a community diagnosis. After the data were collected, a community meeting was held with village residents. Subsequently, interventions were carried out through the development of printed media in the form of leaflets and posters addressing the identified health problems. Results: Based on seven identified problems, an assessment was conducted using the USG method to determine one priority issue to be addressed and prevented. After discussions involving community leaders and residents of RT 17, the main priority health problem was identified as exposure to cigarette smoke. Conclusion: In RT 17 Dukuh Wonocatur, Banguntapan, Bantul, primary data collection identified various health problems. Through the application of the USG method and discussions with the community, exposure to cigarette smoke was prioritized. The agreed-upon solution was the installation of posters at several locations frequently visited by residents and the distribution of leaflets to each household.